Comparative jurisprudence: A comparative apprasial of western jurisprudence and Islamic jurisprudence - Ansari, Abdul Haseeb (Serials Publications, 2018)
Jurisprudence is a well-reconnoitred and well-conversed subject matter of intellectual discourses and writings. There are copious materials covering various facets of jurisprudence in both the disciples, Islamic and Western. But there are scarcer materials comparing important aspects of various intricate but contemporary issues, e.g. rights of women. The author of the book 'Comparative Jurisprudence' has made a potent endeavour to discuss and compare, wherever possible, socio-legal and pure legal issues. The book is distinctive in that sense. It is a useful work for legal scholars, researchers and policymakers.